Behavior and strength of reinforced reactive powder concrete beams under impact loadings - Fadhil, Ibtihal; K. Kadhem, Ayad; Salih, Nisreen (International Journal of Engineering and Technology, 2018)
Reactive powder concrete is a new concrete that has been used in recent years because of many advantages. The use of reactive powder concrete in structural elements such as beams provides higher compressive strength, higher modulus of elasticity, durable concrete and increasing the concrete ductility, so that the concrete has high resistance against tensile stress. The experimental tests of the reinforced concrete beams under the effects of impact loadings are investigated in this paper. The parameters being adopted in present paper are steel fiber of (1, 1.5 and 2%) by volume, dropped mass and height of drop. The reinforced concrete specimens were tested under impact load by one strike only. The test results indicate that the impact force increased when the compressive strength of concrete increased that when the steel fiber ratio becomes more and the deflection has become less.Â Â